Rapid Exclusion of Acute Myocardial Injury and Infarction With a Single High-Sensitivity Cardiac Troponin T in the Emergency Department: A Multicenter United States Evaluation. Issue 23 (10th May 2022) - Sandoval, Yader; Lewis, Bradley R.; Mehta, Ramila A.; Ola, Olatunde; Knott, Jonathan D.; De Michieli, Laura; Akula, Ashok; Lobo, Ronstan; Yang, Eric H.; Gharacholou, S. Michael; Dworak, Marshall; Crockford, Erika; et al.
Abstract : Background: There are good data to support using a single high-sensitivity cardiac troponin T (hs-cTnT) below the limit of detection of 5 ng/L to exclude acute myocardial infarction. Per the US Food and Drug Administration, hs-cTnT can only report to the limit of quantitation of 6 ng/L, a threshold for which there are limited data. Our goal was to determine whether a single hs-cTnT below the limit of quantitation of 6 ng/L is a safe strategy to identify patients at low risk for acute myocardial injury and infarction. Methods: The efficacy (proportion identified as low risk based on baseline hs-cTnT<6 ng/L) of identifying low-risk patients was examined in a multicenter (n=22 sites) US cohort study of emergency department patients undergoing at least 1 hs-cTnT (CV Data Mart Biomarker cohort). We then determined the performance of a single hs-cTnT<6 ng/L (biomarker alone) to exclude acute myocardial injury (subsequent hs-cTnT >99th percentile in those with an initial hs-cTnT<6 ng/L). The clinically intended rule-out strategy combining a nonischemic ECG with a baseline hs-cTnT<6 ng/L was subsequently tested in an adjudicated cohort in which the diagnostic performance for ruling out acute myocardial infarction and safety (myocardial infarction or death at 30 days) were evaluated. Results: A total of 85 610 patients were evaluated in the CV Data Mart Biomarker cohort, among which 24 646 (29%) had a baseline hs-cTnT<6 ng/L. Women were more likely than men to have hs-cTnT<6 ng/L (38% versus 20%, P <0.0001). Among 11 962 patients with baseline hs-cTnT<6 ng/L and serial measurements, only 1.2% developed acute myocardial injury, resulting in a negative predictive value of 98.8% (95% CI, 98.6–99.0) and sensitivity of 99.6% (95% CI, 99.5–99.6). In the adjudicated cohort, a nonischemic ECG with hs-cTnT<6 ng/L identified 33% of patients (610/1849) as low risk and resulted in a negative predictive value and sensitivity of 100% and a 30-day rate of 0.2% for myocardial infarction or death. Conclusions: A single hs-cTnT below the limit of quantitation of 6 ng/L is a safe and rapid method to identify a substantial number of patients at very low risk for acute myocardial injury and infarction.